2014
DOI: 10.1177/1049909114565658
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care for People With Cancer From Ethnic Minority Groups

Abstract: EOL care differences among ethnic/racial minority cancer patients were found in the processes, preferences, and beliefs regarding their care. Further steps are needed to explore the exact causes of differences, yet possible explanations include religious or cultural differences, caregiver respect for patient autonomy, access barriers, and knowledge of EOL care options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
175
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(182 citation statements)
references
References 35 publications
(206 reference statements)
6
175
0
1
Order By: Relevance
“…In particular, racial/ethnic disparities both in receipt of aggressive care and hospice use have been documented extensively. Indeed, compared to others, minority patients are more likely to choose aggressive care [19] or to be hospitalized after being enrolled in hospice [20], and less likely to enroll in hospice care [17,2124]. However, seldom have previous studies examined disparities in the specific context of geriatric patients with cancer presenting with multimorbidity (MM), defined here as the co-occurrence of not only chronic conditions but also functional limitations and geriatric syndromes [25].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, racial/ethnic disparities both in receipt of aggressive care and hospice use have been documented extensively. Indeed, compared to others, minority patients are more likely to choose aggressive care [19] or to be hospitalized after being enrolled in hospice [20], and less likely to enroll in hospice care [17,2124]. However, seldom have previous studies examined disparities in the specific context of geriatric patients with cancer presenting with multimorbidity (MM), defined here as the co-occurrence of not only chronic conditions but also functional limitations and geriatric syndromes [25].…”
Section: Introductionmentioning
confidence: 99%
“…In their review on contextual factors influencing ACP uptake in palliative care, Lovell and Yates concluded that factors influencing the uptake of ACP are "complex and multifaceted, reflecting the diverse and often competing needs of patients, health professionals, legislature, and health systems" (Lovell & Yates, 2014). Indeed, several papers and reviews have looked at the many barriers to the implementation of ACP, for example cultural aspects, timing of ACP discussions, sometimes in relation to specific medical conditions (Fritz et al, 2016), shifts in preferences over time, and the attitudes and beliefs of healthcare providers (Auriemma et al, 2014;Lopresti, Dement, & Gold, 2016;Lovell & Yates, 2014) reiterating the complexity of the ACP process.…”
mentioning
confidence: 99%
“…Disagreements between family or other surrogates and individual preferences are well documented, yet little information exists as to how family or surrogate characteristics may be associated with EOL expenditures. Additionally, providers make assumptions based on presumed EOL preference differences according to race and thereby contribute to overall Medicare expenditures by providing unwanted life‐sustaining care . Further research is needed to determine whether including family‐ or caregiver‐ and provider‐level factors explains more of the variation in EOL expenditures between racial and ethnic groups.…”
Section: Discussionmentioning
confidence: 99%